The Caine mutiny [videorecording (DVD)] - Dmytryk, Edward; Bogart, Humphrey, 1899-1957; Ferrer, José, 1912-1992; Johnson, Van, 1916-2008; MacMurray, Fred, 1908-1991; Francis, Robert, 1930-1955; Wynn, May, 1928-2021-; Wouk, Herman, 1915-2019- (Sony Pictures Home Entertainment, 2007)
During World War II, onboard a ship in the U.S. Pacific Fleet, an event occurs unlike any that the United States Navy has ever experienced. A ship's captain is removed from his command by his executive officer in an apparent outright act of mutiny. As the trial of the mutineers unfold, it comes to light that Captain Queeg was mentally unstable, perhaps even insane. The Navy must then decide if the Caine Mutiny is a criminal act or an act of courage to save a ship from destruction at the hands of her captain.